Methodological Considerations for Preterm Birth Research - Malaba, Thokozile R.; Newell, Marie-Louise; Myer, Landon; Ramokolo, Vundli (Frontiers in Global Women's Health, 2022)
Complications from preterm birth are a leading cause of infant mortality, with long-term implications for morbidity and quality of life of preterm infants. There are many important risk factors for preterm births however in this article, we focus on the maternal infection etiological pathway, given its significance in low-to-middle income countries. In high preterm birth settings such as sub-Saharan Africa, maternal HIV infection and antiretroviral therapy (ART) use have been associated with an increased risk of preterm births. Consequently, we highlight methodological considerations related to selection and measurement bias in preterm birth research. We further illustrate the potential impact of these biases in studies investigating the relationship between HIV/ART and preterm births. We also briefly discuss issues related to population-level estimations based on routinely collected clinical or civil registration data. We conclude by emphasising the importance of strengthening of antenatal care services to improve quality of population data as well as optimising current and future study designs, by taking into account the important methodological considerations described in this article.